RISK OF HAEMORRHAGIC COMPLICATIONS OF RETROPUBIC SURGERY IN FEMALES: ANATOMIC REMARKS - Jaburek, Ladislav; Jaburkova, Jana; Lubusky, Marek; Prochazka, Martin (Biomedical papers, 2011)
Background: An anatomic study.Objective: To point out the risk of bleeding during retropubic surgery in females.Methods: A pelvic dissection, preparation of vessels and photodocumentation in colour.Results: A detailed representation of topographic vessel relations in pelvic and retropubic regions is presented. This could be used as an authentic visual aid for postgraduate training in urogynaecological surgery.Conclusion: This study highlights the risk of vascular lesions common to all suspensory surgical procedures for female stress urinary incontinence. Apart from paraurethral vessels, the vessels of the urinary bladder, the paravesical plexuses, the retropubic anastomosis and the external iliac vessles can be injured in surgery. Preceeded by training at an accredited urogynaecologic centre, TVT can be considered a safe method. Introduction of other modifications such as the transobturator system (namely the + "inside-out" method) makes all urogynaecological surgical procedures much safer.
Keywords: Urogynaecology/Retropubic surgery/Bleeding/Corona mortis/TVT